1519. Reduction of healthcare-associated viral infections during COVID-19 pandemic. (31st December 2020) - Handy, Lori; Ehritz, Carly; Hei, Hillary; Brennan, Lauren K; Wilson, Kimberly; O'Callaghan, Kevin P; Coffin, Susan E; Coffin, Susan E; Sammons, Julia S
Abstract: Background: Healthcare-associated viral infections (HAVI) are a common cause of preventable harm, particularly in pediatric patients. We utilized routine hospital-wide surveillance data for HAVIs at a quaternary care pediatric hospital in order to assess the impact of enhanced public health measures on rates of HAVI at our institution during the COVID-19 pandemic. Methods: Patient cases of HAVI were detected through routine house-wide microbiologic surveillance. Compliance with our institutional prevention bundle, which includes hand hygiene, appropriate use of isolation precautions and personal protective equipment (PPE), maintaining a clean and clutter free environment, employee illness policy, and restrictions on sick visitors, was measured through use of Kamishibai-card rounding. Results: During the most acute period of the COVID-19 pandemic, intensification of the majority of elements of the HAVI bundle occurred by nature of our institutional response, including use of PPE monitors in certain locations, increased used of eye protection, universal masking for staff and caregivers, re-education for employees on not coming to work sick, and further restrictions to visitation. The monthly HAVI rate in the acute phase of the COVID-19 pandemic was lower in March (0.76), April (0.27) and May (0.0) 2020 compared to the same time period last year (0.8, 0.8, 0.56). Bundle compliance during those months in 2020 was 83%, 89%, and 100%, respectively. In May, zero HAVIs were identified. (Figure 1) Healthcare-associated viral infections rate and bundle compliance after COVID-19 prevention measures Conclusion: The intensification of routine infection prevention practices aimed at minimizing the transmission of COVID-19 may also reduce rates of HAVI. During our COVID response, we identified a decrease in our institutional HAVI rate compared to the same time last year, reaching lower special cause in May with a rate of 0. We will have ongoing measurement of the HAVI rate throughout the pandemic to determine if this reduction can be sustained and understand which intensified bundle elements need to be maintained in non-pandemic hospital operations. Disclosures: All Authors : No reported disclosures